(The Isolation of Citronelle Oil Components by Fractional Distillation on Kilo Scale) - Moestafa, Achmad (Warta Industri Hasil Pertanian, 1990)
Citronellal, citronellol and geraniol are then main components of citronella oil. They can be isolated by chemical means or fractional distillation. This study employed the second method. A perforated plate colomn, bubble cup type was used and the operation was carried out on 1:3 reflux ratio. The result showed that citronella was distilled as the first and second fraction after 85 min. The third fraction was a mixture of all components.It took 60 min. to produce 300 ml of liquid; the boiling range was 84-87 C and the separation was poor. It can be said that other than boiling point, the time of distillation should also be managed carefully. The separation depend on the time of distillation and the value of reflux ratio.